2016
DOI: 10.1118/1.4941016
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Method to correlate whole‐specimen histopathology of radical prostatectomy with diagnostic MR imaging

Abstract: Purpose: Validation of MRI-guided tumor boundary delineation for targeted prostate cancer therapy is achieved via correlation with gold-standard histopathology of radical prostatectomy specimens. Challenges to accurate correlation include matching the pathology sectioning plane with the in vivo imaging slice plane and correction for the deformation that occurs between in vivo imaging and histology. A methodology is presented for matching of the histological sectioning angle and position to the in vivo imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…However, to assist in correlation with in vivo diagnostic imaging, pathology sectioning was carried out parallel to the in vivo imaging plane (axial to the endorectal coil). The registration steps were carried out in Matlab: 1) The high resolution 3D isotropic T2w data was resampled at the axial oblique angle that best matched in vivo imaging, and the angle was chosen in the manner described in (McGrath et al , 2016), where the distances from the urethra to the anterior, posterior, left and right outer edges of the prostate were measured and compared; 2) The digitized histology slides were visually matched and rigidly registered to the resampled T2w ex vivo images, by finding the best match with regard to the position of the urethra and the shape of the prostate boundary; 3) A digital tumor volume was created from the co-registered histology images through 3D interpolation; 4) The tumor volume was digitally resampled to the ex vivo MRE slice angle. The estimated angle between the in vivo and ex vivo prostate imaging slice planes for all four clinical specimens was on average 18(±9)°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to assist in correlation with in vivo diagnostic imaging, pathology sectioning was carried out parallel to the in vivo imaging plane (axial to the endorectal coil). The registration steps were carried out in Matlab: 1) The high resolution 3D isotropic T2w data was resampled at the axial oblique angle that best matched in vivo imaging, and the angle was chosen in the manner described in (McGrath et al , 2016), where the distances from the urethra to the anterior, posterior, left and right outer edges of the prostate were measured and compared; 2) The digitized histology slides were visually matched and rigidly registered to the resampled T2w ex vivo images, by finding the best match with regard to the position of the urethra and the shape of the prostate boundary; 3) A digital tumor volume was created from the co-registered histology images through 3D interpolation; 4) The tumor volume was digitally resampled to the ex vivo MRE slice angle. The estimated angle between the in vivo and ex vivo prostate imaging slice planes for all four clinical specimens was on average 18(±9)°.…”
Section: Methodsmentioning
confidence: 99%
“…This study reports the MRE data for the clinical prostatectomy specimens, and the MRI parameter (T 1 , T 2 and ADC) data for both the canine and clinical specimens, and further analyzes and compares the MRE data with the MRI parameters for the canine and clinical specimens. The processes described for the clinical specimens form part of a pathology correlation pipeline described in (McGrath et al , 2016). …”
Section: Introductionmentioning
confidence: 99%
“…A limitation of this approach is that an anatomic segment of the prostate contains both transition and peripheral zones of the gland, which can contain unique nonmalignant pathology. Further development of a registering method between histologic tumor annotations and radiologic imaging is desirable but still in an experimental stage . Third, ex vivo imaging results differ from the results acquired under in vivo conditions; therefore, clinical applicability is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Further development of a registering method between histologic tumor annotations and radiologic imaging is desirable but still in an experimental stage. [26][27][28] Third, ex vivo imaging results differ from the results acquired under in vivo conditions; therefore, clinical applicability is limited. Contributing factors include (1) 9.4T magnet at room temperature versus 1.5T or 3T magnet at body temperature, (2) 500-Hz shear waves ex vivo versus 60-120 Hz in vivo, and (3) no surrounding soft tissue ex vivo versus substantial attenuation in a clinical setting.…”
Section: Limitationsmentioning
confidence: 99%
“…They showed that preoperative MRI datasets matched confidently with histopathology using uniform slice thickness and slice angles. Furthermore, different devices have been developed for sectioning prostatectomy specimen, that facilitate comparison between histology and in vivo MRI [10,11]. The device present in this work, allows for a similar comparison between MR Images and gross pathologic assessment.…”
Section: Discussionmentioning
confidence: 99%